Evaluation of slope stability under water and seismic load through the Minimum Lithostatic Deviation method - Paparo, Maria Ausilia <1983> (Alma Mater Studiorum - Università di Bologna, 2014)

(untitled)
The main objective of this thesis is to obtain a better understanding of the methods to assess the stability of a slope. We have illustrated the principal variants of the Limit Equilibrium (LE) method found in literature, focalizing our attention on the Minimum Lithostatic Deviation (MLD) method, developed by Prof. Tinti and his collaborators (e.g. Tinti and Manucci, 2006, 2008). We had two main goals: the first was to test the MLD method on some real cases. We have selected the case of the Vajont landslide with the objective to reconstruct the conditions that caused the destabilization of Mount Toc, and two sites in the Norwegian margin, where failures has not occurred recently, with the aim to evaluate the present stability state and to assess under which conditions they might be mobilized. The second goal was to study the stability charts by Taylor and by Michalowski, and to use the MLD method to investigate the correctness and adequacy of this engineering tool.